Mediators for Basic Sciences Learning Through Graphic Interfaces (2010)
When carrying out the teaching process it is very important to consider the use of resources, especially those related to didactic means in order to make it easier both the teaching and learning process. This article introduces the goals and strengths trough the implementation of user´s graphical interfaces as didactic resources that help the understanding of different concepts in Mathematics and physics. Matlab’s Tool GUIDE is used (Barragán, 2006), for the applications design whose aims are, among others, contrasting concepts about Mathematics, Calculus, and Physics. These mediators apart of helping the comprehension of fundamental concepts on these disciplines compare the results as a key aspect when looking for application concepts of the mentioned area. It is exposed the way how these didactic resources are really meaningful as a supporting strategy in order to improve the comprehension processes on concepts about Calculus and Physics, since they allow the activation of cognitive schemas from previous knowledge and the verification of results in a practical way. It is also possible to observe how these tools improve students’ motivation, because they become didactic resources which develop thought structures that stimulate meaningful learning (Molina, 2009).